Knowledge Construction In Ecological Sustainability Of The Women - Jannah, Raudlatul; Handayani, Baiq Lily; Yuswadi, Hary; Hidayat, Nurul (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The background of this research about environmental problems, such as loss of soil fertility, depletion of groundwater, river pollution, waste management, seem to be a phenomenon that is happening right now. Human dependence on nature is increasingly critical, but it is not balanced with an awareness of environmental preservation. The purpose of this research is to find out and describe the construction of women's ecological sustainability in Jember. This construction includes water management, power management, transportation use, and waste management. This study uses a qualitative method with interviews as a data collection technique. The informants of this study were selected from six villages in Jember, namely Karangrejo, Antirogo, Tegalgede, Kalisat, Sumbersari, and TegalBesar villages. This study uses a purposive method, especially housewives whose activities relate to these indicators. The results showed that women had limited knowledge construction about ecological sustainability. This construction develops based on daily experience and individual knowledge of the ecological preservation models around them. Therefore, household waste is often found scattered in the ecosystem.